PENERAPAN MASTERY LEARNING PADA PEMBELAJARAN - Zen Istiarsono, (Pelangi Ilmu, 2009)
Abstract Specifically, mastery learning is a method whereby students are not advanced to a subsequent learning objective until they demonstrate proficiency with the current one. Mastery learning may be implemented as teacher-paced group instruction, one-to-one tutoring, or self-paced learning with programmed materials. It may involve direct teacher instruction, cooperation with classmates, or independent learning. It requires well-defined learning objectives organized into smaller, sequentially organized units. Individualized instruction, has some elements in common with mastery learning, although it dispenses with group activities, in favor of allowing more able or more motivated students to progress ahead of others and maximizing teacher interaction with those students who need the most assistance.